2017
DOI: 10.1186/s12887-017-0842-8
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and opportunities of whole blood bilirubin measurements by GEM premier 4000®

Abstract: BackgroundNeonatal hyperbilirubinemia has traditionally been screened by either total serum bilirubin or transcutaneous bilirubin. Whole blood bilirubin (TwB) by the GEM Premier 4000® blood gas analyzer (GEM) is a relatively new technology and it provides fast bilirubin results with a small sample volume and can measure co-oximetry and other analytes. Our clinical study was to evaluate the reliability of TwB measured by the GEM and identify analytical and clinical factors that may contribute to possible bias.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…Although Hb F and Hb A (majority of adult hemoglobin) have a slightly different light absorption spectra, it is important enough to be taken into account in the multi-component analysis of hemoglobin derivatives [ 18 , 19 ]. The inaccurate neonatal hemoglobin on the GEM observed in this study may also account for the bias of bilirubin measurements between blood gas analyzers and chemistry analyzers as seen in Wang’s study [ 8 ].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although Hb F and Hb A (majority of adult hemoglobin) have a slightly different light absorption spectra, it is important enough to be taken into account in the multi-component analysis of hemoglobin derivatives [ 18 , 19 ]. The inaccurate neonatal hemoglobin on the GEM observed in this study may also account for the bias of bilirubin measurements between blood gas analyzers and chemistry analyzers as seen in Wang’s study [ 8 ].…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the GEM underestimated bilirubin at low levels and overestimated bilirubin at high levels. It also identified that the GEM underestimated bilirubin at high hemoglobin levels [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neonatal bilirubin has traditionally been measured by either total serum bilirubin or transcutaneous bilirubin (7). The application of a biochemical analyzer for venous blood bilirubin is currently considered a more reliable clinical method (8,9).…”
Section: Discussionmentioning
confidence: 99%